Staging Revolution : Artistry and Aesthetics in Model Beijing Opera during the Cultural Revolution - Fan, Xing (Book collections on Project MUSE., 2018)
Staging Revolution refutes the deep-rooted notion that art overtly in the service of politics is by definition devoid of artistic merit. As a prominent component shaping the culture of the Cultural Revolution, model Beijing Opera (jingju) is the epitome of art used for political ends. Arguing against commonly accepted interpretations, Xing Fan demonstrates that in a performance of model jingju, political messages could only be realized through the most rigorously formulated artistic choices and conveyed by performers possessing exceptional techniques. Fan contextualizes model jingju at the intersection of history, artistry, and aesthetics. Integral to jingju's interactions with politics are the practitioners' constant artistic experimentation to accommodate the modern stories and characters within the jingju framework and the eventual formation of a new sense of beauty. Therefore, a thorough understanding of model jingju demands close attention to how the artists resolved actual production problems, which is a critical perspective missing in earlier studies. This book provides exactly this much-needed dimension of analysis by scrutinizing the decisions made in the real, practical context of bringing dramatic characters to life on stage and by examining how major artistic elements interacted with one other, sometimes harmoniously, sometimes antagonistically. Such an approach necessarily places jingju artists center stage. Making use of first-person accounts of the creative process, including numerous interviews conducted by the author, Fan presents a new appreciation of a lived experience that, on a harrowing journey of coping with political interference, was also filled with inspiration and excitement.